Seni Kaligrafi Dalam Perspektif Filsafat Seni - Siti Nur Rafiza; Sayed Muhammad Ichsan (Jurnal Shaf, 2024)
Beauty or often known as aesthetics is not only in the form of carvings or shapes in a painting, but in the art of calligraphy, writing has its own beauty which has meaning in every writing written by a calligrapher. This research aims to find out how the art of calligraphy is from an art philosophy perspective. The research method used is library research with a descriptive qualitative approach. The results of this research are that the philosophy of art views calligraphy as a means of conveying meaning, beauty and spiritual feelings through the form, space and style of writing chosen. In fact, calligraphy is often valued for its ability to combine visual beauty with philosophical or religious meaning.